Fresno County Women Lawyers' Installation of Officers Dinner Meeting - Watkins, Howard::::::::: (1988)
Fresno County Women Lawyers President Karen Kern speaking; front table: ?, Fran Christiansen, ALJ Ivy Roberts; Back table: Joan Wilkie, Judge Herbert Levy, Regina Leary, William Coleman, Judge Gary Austin, Doris Coleman, Karen Burt, and Jim Wilkie Dinner meeting in upstairs loft area